Social cohesion in the Russian society: Results of the empirical study - V. A. Tupikova; E. K. Misiautova; L. E. Murzikov (RUDN journal of Sociology)
The article presents the results of the study of the perception of social cohesion in today’s Russia. The study consisted of two stages - expert and all-Russian - and was conducted with methods of expert assessments, focus groups and online survey in order to reconstruct a twosided view of social cohesion - from the point of view of experts (representatives of “close-knit communities”, who are involved in collective activities; such communities aim at uniting people within “person-to-person” activities, i.e. within the framework of providing assistance, following common ideals and values, contributing to a common cause) and the population as a whole. The assessments of these two categories of respondents differ significantly: experts consider the level of social cohesion in the Russian society as much lower, highlighting such factors contributing to solidarity as common values and traditions, a common goal or a problem, a common cause, a common enemy (not necessarily an external aggressor, certain difficulties or crisis situations are sufficient); responsibility, courage, motivation, personal interest; leaders who are ready to take responsibility and influence others. In the public opinion, social cohesion as defined primarily as mutual assistance and is also associated with common values and unity of opinion; Russians highly value the current level of mutual assistance, unity and social security. The main reasons for unity with other citizens in the Russian public opinion are the common territory of residence (state and small homeland) and common language. At the theoretical stage, the study showed that the problem of operationalization of concepts related to social cohesion remains, although most scientists define it mainly as solidarity based on common values. In the study, the authors conducted a comparative analysis of such key concepts as “social cohesion” and “solidarity”, including in the context of their classical and today’s interpretations.